2010
DOI: 10.3920/bm2009.0025
|View full text |Cite
|
Sign up to set email alerts
|

Xylo-oligosaccharides enhance the growth of bifidobacteria and Bifidobacterium lactis in a simulated colon model

Abstract: A semi-continuous, anaerobic colon simulator, with four vessels mimicking the conditions of the human large intestine, was used to study the fermentation of xylo-oligosaccharides (XOS). Three XOS compounds and a xylan preparation were fermented for 48 hours by human colonic microbes. Fructo-oligosaccharides (FOS) were used as a prebiotic reference. As a result of the fermentation, the numbers of Bifidobacterium increased in all XOS and xylan simulations when compared to the growth observed in the baseline simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 50 publications
4
58
1
4
Order By: Relevance
“…In in vitro studies only comprising prebiotics, i.e. melibiose, isomaltulose, cellobiose, xylobiose, maltotriose, raffinose and oat β-glucans, increases in acetic acid were reported to be between two and six times higher as compared to controls and for butyric acid the highest concentrations observed were four times higher as compared to control [60][64]. These increases in concentrations of acetic and butyric acids are, however, lower than the increases observed for all synbiotic combinations investigated in the present study where concentrations were three to eight times higher for both acetic and butyric acids as compared to control, The findings emphasize that a synergistic effect may be obtained when combining these prebiotic candidates with the probiotic strains NCFM and Bl-04.…”
Section: Discussionmentioning
confidence: 99%
“…In in vitro studies only comprising prebiotics, i.e. melibiose, isomaltulose, cellobiose, xylobiose, maltotriose, raffinose and oat β-glucans, increases in acetic acid were reported to be between two and six times higher as compared to controls and for butyric acid the highest concentrations observed were four times higher as compared to control [60][64]. These increases in concentrations of acetic and butyric acids are, however, lower than the increases observed for all synbiotic combinations investigated in the present study where concentrations were three to eight times higher for both acetic and butyric acids as compared to control, The findings emphasize that a synergistic effect may be obtained when combining these prebiotic candidates with the probiotic strains NCFM and Bl-04.…”
Section: Discussionmentioning
confidence: 99%
“…Some intestinal bacterial strains are able to grow on XOS, yet numerous studies have demonstrated that the ability to utilize these oligosaccharides varies considerably among these bacteria (3,25,29). Moreover, a recent semicontinuous, anaerobic colon simulator study demonstrated that growth on XOS can also result in decreased levels of pathogenic strains, an increase in the levels of short-chain fatty acids, and a decrease in the concentrations of branched-chain amino acids, data that indicate a balanced microflora (11).…”
mentioning
confidence: 99%
“…A fresh fecal sample obtained from a healthy, lean human donor (multiple donors were avoided to minimize variation), who had not received antibiotic treatment prior to the study, was diluted with synthetic ileal fluid, used as basic medium (BM; previously described by Mäkeläinen et al 27). Inoculum was filtered through a 0.3 mm mesh and incubated for 24 h anaerobically at 37°C before being added to medium containing prebiotic candidates (2% w/v and lyophilized Lactobacillus acidophilus NCFM (1 × 10 9 cells per inoculum).…”
Section: Methodsmentioning
confidence: 99%